Bridging the Bridging Imidazolate in the Bimetallic Center of the Cu/Zn SOD1 and ALS - Timucin, Ahmet Can; Cinaroglu, Suleyman Selim; Sezerman, Osman Ugur; Timucin, Emel (Frontiers in Chemistry, 2021)
Metallation status of human Cu/Zn superoxide dismutase 1 (SOD1) plays a pivotal role in the pathogenesis of amyotrophic lateral sclerosis (ALS). All of the amino acids found in the bimetallic center have been associated with ALS except for two positions. H63 which forms the bridging imidazolate ion in the bimetallic center and K136 which is not directly involved in coordination but located in the bimetallic center were not reported to be mutated in any of the identified ALS cases. In this study, we investigated the structure and flexibility of five SOD1 variants by using classical molecular dynamics simulations. These variants include three substitutions on the non-ALS-linked positions; H63A, H63R, K136A and ALS-linked positions; G37R, H46R/H48D. We have generated four systems for each variant differing in metallation and presence of the intramolecular disulfide bond. Overall, a total of 24 different dimers including the wild-type were generated and simulated at two temperatures, 298 and 400 K. We have monitored backbone mobility, fluctuations and compactness of the dimer structures to assess whether the hypothetical mutations would behave similar to the ALS-linked variants. Results showed that particularly two mutants, H63R and K136A, drastically affected the dimer dynamics by increasing the fluctuations of the metal binding loops compared with the control mutations. Further, these variants resulted in demetallation of the dimers, highlighting probable ALS toxicity that could be elicited by the SOD1 variants of H63R and K136A. Overall, this study bridges two putative SOD1 positions in the metallic center and ALS, underlining the potential use of atomistic simulations for studying disease variants.